Exploring Biomarkers Beyond Exercise Testing: The Impact of Smoking on Cardiovascular and Pulmonary Health among CKD Patients - Kashefizadeh, Alireza; Mehravaran, Hossein; Samavat, Shiva; Nafar, Mohsen; Amini, Hossein; Dalili, Nooshin (Novelty in Biomedicine, 2024)
Background: Chronic Kidney Disease (CKD) patients often face complex health challenges, including cardiovascular and pulmonary issues. Smoking is a recognized risk factor for these conditions, but its specific impact on CKD patients remains less understood. Materials and Methods: In this cross-sectional study, we investigated the relationship between smoking habits and cardiopulmonary health among CKD patients. We examined baseline characteristics, including demographics, medical history, and biochemical markers, in a cohort of CKD patients. Cardiopulmonary parameters were assessed during exercise testing, including oxygen consumption, ventilation rates, ventilation-perfusion matching markers, and oxygen saturation levels. Results: Our findings revealed no statistically significant differences in cardiopulmonary parameters between smokers and non-smokers within the CKD patient population. This suggests that the relationship between smoking and exercise capacity in CKD patients is complex and influenced by multiple factors. Our analysis of demographics, comorbidities, and medication history provided critical context for interpreting these results. Conclusion: This study contributes to our understanding of the intricate relationship between smoking habits and cardiopulmonary health in CKD patients. While smoking is recognized as a risk factor, its specific impact on exercise capacity within this population may be influenced by individual variables. Further research is needed to explore these relationships in larger and more diverse cohorts. These findings underscore the importance of considering multiple variables when assessing the impact of smoking on the health of CKD patients.